AXIN1 knockout does not alter AMPK/mTORC1 regulation and glucose metabolism in mouse skeletal muscle. (19th May 2021) - Li, Jingwen; Knudsen, Jonas R.; Henriquez‐Olguin, Carlos; Li, Zhencheng; Birk, Jesper B.; Persson, Kaspar W.; Hellsten, Ylva; Offergeld, Anika; Jarassier, William; Le Grand, Fabien; Schjerling, Peter; Wojtaszewski, Jørgen F.P.; et al.
Abstract : Key points: Tamoxifen‐inducible skeletal muscle‐specific AXIN1 knockout (AXIN1 imKO) in mouse does not affect whole‐body energy substrate metabolism. AXIN1 imKO does not affect AICAR or insulin‐stimulated glucose uptake in adult skeletal muscle. AXIN1 imKO does not affect adult skeletal muscle AMPK or mTORC1 signalling during AICAR/insulin/amino acid incubation, contraction and exercise. During exercise, α2/β2/γ3AMPK and AMP/ATP ratio show greater increases in AXIN1 imKO than wild‐type in gastrocnemius muscle. Abstract: AXIN1 is a scaffold protein known to interact with >20 proteins in signal transduction pathways regulating cellular development and function. Recently, AXIN1 was proposed to assemble a protein complex essential to catabolic‐anabolic transition by coordinating AMPK activation and inactivation of mTORC1 and to regulate glucose uptake‐stimulation by both AMPK and insulin. To investigate whether AXIN1 is permissive for adult skeletal muscle function, a phenotypic in vivo and ex vivo characterization of tamoxifen‐inducible skeletal muscle‐specific AXIN1 knockout (AXIN1 imKO) mice was conducted. AXIN1 imKO did not influence AMPK/mTORC1 signalling or glucose uptake stimulation at rest or in response to different exercise/contraction protocols, pharmacological AMPK activation, insulin or amino acids stimulation. The only genotypic difference observed was in exercising gastrocnemius muscle, where AXIN1 imKO displayed elevated α2/β2/γ3 AMPK activity and AMP/ATP ratio compared to wild‐type mice. Our work shows that AXIN1 imKO generally does not affect skeletal muscle AMPK/mTORC1 signalling and glucose metabolism, probably due to functional redundancy of its homologue AXIN2. Key points: Tamoxifen‐inducible skeletal muscle‐specific AXIN1 knockout (AXIN1 imKO) in mouse does not affect whole‐body energy substrate metabolism. AXIN1 imKO does not affect AICAR or insulin‐stimulated glucose uptake in adult skeletal muscle. AXIN1 imKO does not affect adult skeletal muscle AMPK or mTORC1 signalling during AICAR/insulin/amino acid incubation, contraction and exercise. During exercise, α2/β2/γ3AMPK and AMP/ATP ratio show greater increases in AXIN1 imKO than wild‐type in gastrocnemius muscle.